(untitled) (Periphērica, 2025)
Marcelo Piñeyro’s 1995 film Caballos salvajes chronicles the five-day journey of two fugitives, José and Pedro, from Argentina’s capital city of Buenos Aires to the nation’s southern region after a holdup gone awry. The two runaways – Pedro, a young employee originally held up by José, an aging anarchist – develop an unlikely friendship. Thanks to intense media interest, José and Pedro become national heroes, understood as modern day Robin Hood figures after giving the stolen money away to a community of recently laid off chemical plant workers. At a critical moment early in the film, Pedro incredulously asks José why he has turned the entire episode into a question of politics. José resolutely refuses this accusation, stopping the conversation to exit the car they are traveling in, circle it brusquely, and re-enter, scolding his young travel companion: “¿Cómo voy a hablar de política? No estoy hablando de política. Hablo del mundo en el que estás viviendo.” Taking this decisive scene as a starting point, I argue that what is at stake for José throughout the film is what Alberto Moreiras has termed “infrapolitics.” Moreiras has described infrapolitics as “la diferencia absoluta entre vida y política,” arguing for a theoretical stance which acknowledges that politics does not (indeed, cannot) exhaust life itself. I will argue that the film offers us the notion that, while politics does mark many aspects of life, there remains a level of experience that cannot be subsumed under any sort of calculative political logic. Caballos salvajes therefore posits a version of José’s anarchist politics that is an-archē-ic, an anarchism that sidesteps anarchism’s paradoxical principal of non-foundation.